Application of expert system diagnosis of color blindness with ishihara method with microsoft vb 6.0 - Verdi Yasin; Peniarsih Peniarsih; Ahmad Gozali; Ifan Junaedi (International Journal of Informatics, Economics, Management and Science (IJIEMS), 2022)
Application Expert System Diagnosis of Color blindness using the Ishihara Method With Microsoft VB 6.0 is a system that makes it easier to diagnose eye disease (color blindness). In developing engineering systems the development of expert system application applications. To facilitate the development of this program application, Researchers use modeling/designing flow chart tools or structured modeling. And designing input systems in the form of Interface Design related mechanisms for the use of applications of this expert system.